Moral Values Found in the Movie “Avengers 1&2” by Joss Whedon - Gilang Lukito Permatasari; Tanti Nur Annisa; Tahrun (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research aims to explore the moral values shown in two Marvel Cinematic Universe films: The Avengers (2012) and Avengers: Age of Ultron (2015). The study uses a qualitative descriptive method and content analysis to identify important moral messages in the characters’ actions, dialogues, and storylines. The results show that both films highlight key moral values such as teamwork, responsibility, selflessness, personal growth, and ethical decision-making. The Avengers often work together to solve problems, showing the value of collaboration. The theme of responsibility is seen in how their actions, especially the creation of Ultron, lead to serious consequences. Characters also show moral strength by making sacrifices for the greater good. Their struggles and growth reflect lessons about doing what is right. These values help the audience understand moral behavior and support character education.